Ethics in Professional Practice: An Education Resource for Health Science Students - Kenny, Belinda; Thomson, Kate; Semaan, Amanda; Di Michele, Laura; Pollard, Natalie; Nicole, Madelyn; Jimenez, Yobelli; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2019)
Ethical practice is a core health science graduate attribute yet ethical reasoning is rarely explicitly taught during professional placements. Our aim was to design an educational resource for health science students to 1) engage students in the topic of ethics and 2) facilitate their skills to identify, manage and communicate ethical issues during professional placements. The Ethics in Professional Practice (EPP) resource was developed using collaborative design-based research by an interprofessional, Work Integrated Learning team. We drew upon Barab and Squire’s (2004) approach, with cycles of design, analysis, redesign and feedback informing resource development. The EPP resource comprises five video case studies that reflect ethical issues from diverse professional practice environments and include perspectives from students, clinical educators, clients and caregivers. The student is cast as a central character who must decide what actions may be taken to resolve ethical conflict. Complementary ethics education resources include reflective questions, guides to ethical reasoning and goal-setting resources. The resource was implemented with a cohort of 15 graduate-entry exercise physiology students and 59 undergraduate speech pathology students from the University of Sydney. Student feedback was utilised to inform resource redesign. Findings indicated that students valued the authentic ethics scenarios but experienced challenges when navigating online learning activities. Redesign focussed on enhancing interactive design features and improving accessibility of learning activities. This project achieved our goals to address ethical sensitivity, reasoning, communication and goals for future ethical practice.